Association between pre‐sarcopenia, sarcopenia, and bone mineral density in patients with chronic hepatitis C - Tatiana Bering; Kiara G.D. Diniz; Marta Paula P. Coelho; Diego A. Vieira; Maria Marta S. Soares; Adriana M. Kakehasi; Maria Isabel T.D. Correia; Rosângela Teixeira; Dulciene M.M. Queiroz; Gifone A. Rocha; Luciana D. Silva (Wiley, 2018)
Abstract Background Preserved skeletal muscle is essential for the maintenance of healthy bone. Loss of bone mineral density (BMD) and muscle strength, considered a predictor of BMD, have been demonstrated in patients with cirrhosis, but they are poorly studied in chronic hepatitis C (CHC) without cirrhosis. Thus, we aimed to evaluate the prevalence of low BMD and its association with body composition, muscle strength, and nutritional status in CHC. Methods One hundred and four subjects [mean age, 50.5 ± 11.3 years; 75.0% males; 67.3% non‐cirrhotic; and 32.7% with compensated cirrhosis] with CHC, prospectively, underwent scanning of the lean tissue, appendicular skeletal muscle mass (ASM), fat mass, lumbar spine, hip, femoral neck, and whole‐body BMD by dual‐energy X‐ray absorptiometry. Muscle strength was assessed by dynamometry. Sarcopenia was defined by the presence of both low, ASM/height2 (ASMI) and low muscle strength according to the European Working Group on Sarcopenia in Older People criteria. The cut‐off points for low ASMI and low muscle strength, for women and men, were < 5.45 and < 7.26 kg/m2 and < 20 and < 30 kg, respectively. According to the adopted World Health Organization criteria in men aged > 50 years, the T‐score of osteopenia is between −1.0 and −2.49 standard deviation (SD) below the young average value and of osteoporosis is ≥−2.5 SD below the young normal mean for men, and the Z‐score of low bone mass is ≤−2.0 SD below the expected range in men aged < 50 years and women in the menacme. Nutritional status evaluation was based on the Controlling Nutritional Status score. Results Low BMD, low muscle strength, pre‐sarcopenia, sarcopenia, and sarcopenic obesity were observed in 34.6% (36/104), 27.9% (29/104), 14.4% (15/104), 8.7% (9/104), and 3.8% (4/104) of the patients, respectively. ASMI was an independent predictor of BMD (P < 0.001). Sarcopenia was independently associated with bone mineral content (P = 0.02) and malnutrition (P = 0.01). In 88.9% of the sarcopenic patients and in all with sarcopenic obesity, BMI was normal. The mid‐arm muscle circumference was positively correlated with ASMI (r = 0.88; P < 0.001). Conclusions This is the first study to demonstrate that ASM is an independent predictor of BMD in CHC. Mid‐arm muscle circumference coupled with handgrip strength testing should be incorporated into routine clinical practice to detect low muscle mass, which may be underdiagnosed when only BMI is used. These findings may influence clinical decision‐making and contribute to the development of effective strategies to screen the musculoskeletal abnormalities in CHC patients, independently of the stage of the liver disease.